Heritability and Response to Recurrent Selection in Two Sweet Corn Varieties - Saleh, Ghizan; Yusop, Mohd Rafii; Yap, Thoo Chai (Universiti Putra Malaysia Press, 1994)
One cycle of simple and full-sib reciprocal recurrent selection programme was conducted on two sweet corn varieties, Manis Madu and Bakti-1, at Universiti Pertanian Malaysia. The objectives of the study were to compare the response to the two selection procedures, and to estimate heritability of some important characters in the two populations. The presence of higher genetic variance in Bakti-1 S1 population (B1S) compared to that of Manis Madu (MMS) showed that B1S1possessed higher genetic variability than MMS. Broad-sense heritability estimates for the characters studied were moderate to high (42.6% to 65. 7%) in the selfed progeny populations, but were low to moderate (20.0 % to 49.2 %) in the crossed progeny populations. After one cycle of selection, simple recurrent selection was found to be more effective in increasing yield in both populations. Simple recurrent selection increased fresh ear yield in Bakti-1 and Manis Madu by 16. 7% and 10.2% respectively, while full-sib reciprocal recurrent selection increased it in Bakti-1 by 5.9 %, but decreased it in Manis Madu by 6.4 %.